Upaya Meningkatkan Hasil Belajar IPS Dengan Model Pembelajaran Kooperatif Tipe Script Pada Siswa Kelas VII SMP Negeri 4 Banda Aceh - Fitriana Fitriana (CV. Rumoh Aceh Publishing, 2025)
This research is based on the problem of teaching and learning process that has not fully involved students actively and independently. Therefore, better LKPD teaching materials are needed so that the teaching and learning process can run optimally. This study aims to determine the use of Student Worksheets (LKPD) in IPS learning in class VII5 SMP Negeri 4 Banda Aceh. The research approach used is Classroom Action Research (PTK). With a qualitative method, the research subjects were 31 students of class VII5. Data collection techniques used observation, tests, and documentation. The results showed that the teacher's activity in the learning process by applying the Script type cooperative model in cycle 1 had reached a good category, which was 62.5%, and in cycle II, it increased to 91.67% with a very good category. Student activities during the learning process by applying the Script type Cooperative model experienced a percentage increase in cycle I with a score of 77.41%, while in cycle II, it increased to 90.32% with a very good category. Student learning outcomes during the learning process with the Script type Cooperative model with socio-cultural themes in cycle I reached a good category with a score of 78.12% and in sub-theme 4 on Socio-Cultural learning in cycle II, it increased to a very good category with a score of 88.54%. Thus, it can be concluded that the application of the learning model using the Script type Cooperative model has successfully improved student learning outcomes in class VII5 SMP Negeri 4 Banda Aceh.